The Effect of a Period of Regular Exercise Activity on the Improvement of Adaptive Behavior in Educable Mentally Retarded Students - Janbaba Aghayinejad; Salar Faramarzi; Mohamad Karimi (University of Tehran, 2015)
Psychological findings show that a lower IQ score than the normal level is notenough to recognize someone as mentally retarded. In addition they have visibleand specific difficulties in their adaptive behaviors. Research on adaptivebehaviors is useful for those with specific needs and if mentally retarded childrenwant to adapt themselves to social life, they should improve their adaptivebehaviors. The current study aimed at determining the effect of a period of regularexercise activity on the improvement of adaptive behavior in 9-15-year-oldeducable mentally retarded students in Lordegan city. From 156 educable mentallyretarded students, 28 students were selected randomly and divided into two groupsof experimental (7 boys and 7 girls) and control (7 boys and 7 girls). Vinlandadaptive behavior Scale (1965) was used as the pretest. Then, the experimentalgroup took part in a period of exercise activity as an intervention program for 2months, 3 sessions every week, 45 minutes per session. The data were analyzed bycovariance using SPSS software (P˂0.05). The results showed a significantdifference between the performance of the two groups in adaptive behavior andsub-skills of socialization, communication, locomotion, dressing self-help, generalself-help and eating self-help (P<0.05) while there was no significant difference insub-skills of occupation and self-direction which showed that a period of regularexercise activity had an effect on the improvement of some sub-skills of adaptivebehavior in experimental group. This approach can be used in rehabilitation andinstruction of mentally retarded children.